Designing flexible work practices for job satisfaction: the relation between job characteristics and work disaggregation in different types of work arrangements. (29th May 2019) - Neirotti, Paolo; Raguseo, Elisabetta; Gastaldi, Luca
Abstract : The literature on flexible work practices has not yet evaluated in detail how the characteristics of a job affect job satisfaction. This study makes a distinction between two types of flexible work practices according to their aims: the accommodation of employees' personal lives (employment practice) and the operational reasons of a firm (work practice). Based on this distinction, we studied how the characteristics of a job, which reflect the use of ICT to support the spatial disaggregation of business processes, influence the relationship between the two types of flexible work practices and job satisfaction. We show, through a survey conducted on 987 workers, that the characteristics of a job that favour work disaggregation positively moderate the influence of flexible work as a work practice on job satisfaction, but they do not moderate the influence of flexible work as an employment practice. The implications for managers, workers and scholars are discussed.